1994
DOI: 10.1172/jci117156
|View full text |Cite
|
Sign up to set email alerts
|

Increased damage to type II collagen in osteoarthritic articular cartilage detected by a new immunoassay.

Abstract: A new immunoassay was developed to detect denaturation of type II collagen in osteoarthritis (OA). A peptide, al(II)-CBllB, located in the CB11 peptide of type II collagen, was synthesized and used to produce a monoclonal antibody (COL2-3/4m) of the IgG,(K) isotype. This reacts with a defined epitope in denatured but not native type II collagen and the a3 chain of type XI collagen. The latter is present in very small amounts (about 1% wt/wt) in cartilage relative to the al (II) chain. By using an enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
511
2
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 571 publications
(542 citation statements)
references
References 25 publications
21
511
2
5
Order By: Relevance
“…This strongly suggests that the activation of potential proteolytic degradation pathways of CII after a joint injury occurs as rapidly as that for aggrecan and other cartilage matrix components. This observation corroborates and extends recent studies by other techniques that have provided evidence for early damage to the cartilage collagen network after joint injury and in OA (26,(32)(33)(34)(35)51).…”
Section: Discussionsupporting
confidence: 91%
“…This strongly suggests that the activation of potential proteolytic degradation pathways of CII after a joint injury occurs as rapidly as that for aggrecan and other cartilage matrix components. This observation corroborates and extends recent studies by other techniques that have provided evidence for early damage to the cartilage collagen network after joint injury and in OA (26,(32)(33)(34)(35)51).…”
Section: Discussionsupporting
confidence: 91%
“…In OA cartilage, the content increased 1.72-fold (P Ͻ 0.001) with 20 l of vector and 1.95-fold (P Ͻ 0.001) with 50 l (a 1.32-fold dose-dependent increase; P Ͻ 0.001). OA cartilage always contained less type II collagen than did normal cartilage, as has been described previously (40,41). Most notably, the content was significantly higher in treated OA cartilage than in control normal cartilage (1.48-fold [P Ͻ 0.001] with 20 l and 1.71-fold [P Ͻ 0.001] with 50 l of vector), probably due to restored SOX9 expression levels (see Figure 3).…”
Section: Expression Of a Sox9 Gene Cassette In Human Articular Chondrsupporting
confidence: 77%
“…Previous work has shown that the removal of proteoglycans and newly synthesised collagen with 4 M guanidine chloride does not irreversibly denature undamaged collagen, and 90% of the denatured collagen is retained within the cross-linked mature collagen fibrils (Hollander et al, 1994(Hollander et al, , 1995Bank et al, 1997). The mean proportion of denatured collagen in the control supraspinatus was 9.9% (range 2.6-16.7%) and did not change significantly across the age range from 18 to 96 years (Fig.…”
Section: Collagen Denaturationmentioning
confidence: 77%